Effects of Urinary Incontinence on QOL of Daily Life in iddle-aged and Elderly Women - SOKABE, Mieko; SHIKATA, Hayako; HUO, Ming; IWASAKI, Akemi; TAJIRI, Kimiko; MARUYAMA, Hitoshi (Rigaku ryoho kagaku, 2020)
[Purpose] To investigate the effects on daily life of urinary incontinence among middle-aged and elderly women. [Participants and Methods] The participants were 262 women over 40 years of age who were living independently. They were given an anonymous paper questionnaire, including the Japanese version of the Incontinence Impact Questionnaire (IIQ) to survey the impact of urinary incontinence on daily life. Descriptive statistics, logistics regression analysis (stepwise method), and factor analysis (principal component analysis, varimax method) were performed using the statistical analysis software, IBM SPSS 25.0. [Results] The average age of the participants was 56.1 ± 10.0 years old: 111 (42.4%) had urinary incontinence, 39 (14.9%) had urinary incontinence in the past, and 112 (42.7%) had none at all. The types of urinary incontinence were: 62 (55.9%) stress urinary incontinence, 13 (11.7%) urge incontinence, and 36 (32.4%) mixed urinary incontinence. In logistic regression analysis, significant factors were: age and the following IIQ items: Q5 (walk, swim, move body with sport), Q11 (go to local gatherings), Q19 (what dress to wear), Q30 (embarrassed) (p<0.01); and Q6 (enjoying entertainment: movies, concerts, etc.), Q8 (going out of the house for more than 30 minutes by car or bus), Q23 (activities restricted due to concerns about smell) (p<0.05). Factor analysis identified (daily life behavior), (leisure behavior) and (interested interpersonal behavior) as relevant factors, and Cronbach’s coefficient for the three factors was 0.975. [Conclusion] Urinary incontinence affected middle-aged and elderly women’s QOL causing psychological anxiety in basic daily living, interpersonal relationships, and social activities.